PENINGKATAN NILAI GIZI MIKRO KUDAPAN LOKAL MELALUI SUBTITUSI TEPUNG IKAN GABUS UNTUK PENCEGAHAN STUNTING DI SULAWESI SELATAN - Nadimin Nadimin; Retno Sri Lestari (Politeknik Kesehatan Makassar, 2019)
ABSTRACT Local snacks are used to being consumed by local people, including children under five, but the local cultural products have unbalanced nutritional content, which generally only contains energy sources. On the other hand, in this area also has fish food ingredients such as